Communicative Approaches in Teaching Spoken English Pre-service Teacher Education in EFL Contexts - Helen Jang (ELT Worldwide: Journal of English Language Teaching, 2014)
Following on the education policy and curriculum innovations for spoken English development, there have been changes as well as challenges in English classrooms in Korea in recent years. In line with the new government policy for pre-service English teacher education, this research explored the nature of teacher learning during the practicum. The aims of this study were to understand the student teachers’ views and experiences of classroom practice period with regard to the use and instruction of spoken English in English classrooms. This research employed two case studies in urban and rural contexts during the intensive period of the practicum.  Data were generated by classroom observations in secondary schools and by in-depth interviews with the student teachers from the communicative perspectives: Contextual factors were taken into consideration in relation to the influence how the student teachers perceived and conducted teaching of speaking in accordance with the curriculum policy presented by the Ministry of Education. Based on the main findings of this research, implications were drawn the relationships between education policy and classroom practice and school contexts.  Suggestions were made as regards effective ways of facilitating teaching and learning spoken English reflecting the diversity and complexity of classroom contexts through context-sensitive approaches in EFL contexts. Keywords: Communicative Approach, Spoken English, Pre-service Teacher Education, EFL Contexts, case study